2011
DOI: 10.1103/physreva.84.013424
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear interference in dissociating of HD+in ultrashort laser fields

Abstract: The dissociation dynamics of HD + molecules is studied theoretically by numerically solving the timedependent Schrödinger equation in which the molecular vibrational and rotational degrees of freedom are included. Based on the Born-Oppenheimer approximation, the ground 1sσ g state and the excited 2pσ u state are taken into account, corresponding to two dissociative channels HD + →D + H + and HD + →H + D + , respectively. Two dissociative nuclear wave packets overlap and interfere after excited by two ultrashor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Substantial effort has been devoted to theoretical studies of the dissociation of the HD + molecular ion [24][25][26][27][28][29][30][31]. For instance, the kinetic energy spectra for the dissociation of this system at high intensities (10 14~1 0 15 W/cm 2 ) were calculated by using the wavepacket method [24,26], which supported the experimental findings that absorption of 4 or 5 photons was occurring at high intensities.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Substantial effort has been devoted to theoretical studies of the dissociation of the HD + molecular ion [24][25][26][27][28][29][30][31]. For instance, the kinetic energy spectra for the dissociation of this system at high intensities (10 14~1 0 15 W/cm 2 ) were calculated by using the wavepacket method [24,26], which supported the experimental findings that absorption of 4 or 5 photons was occurring at high intensities.…”
Section: Introductionmentioning
confidence: 63%
“…For instance, the kinetic energy spectra for the dissociation of this system at high intensities (10 14~1 0 15 W/cm 2 ) were calculated by using the wavepacket method [24,26], which supported the experimental findings that absorption of 4 or 5 photons was occurring at high intensities. Besides the ATD dynamics, many other issues were also investigated, such as the control of the asymmetry branching ratio of the photofragments [28], the interferences between dissociative wavepackets [29], the preparation and probing of the coherent vibrational wavepacket [30], the steering of the electron localization [31], etc. Most of these studies were based on the calculation of the kinetic energy distribution of dissociated fragments, and to the best of our knowledge, the ATD process of the HD + molecular ion has not yet been thoroughly and quantitatively explained in a theory-versus-experiment comparison via a TOF spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…13 and 38–41, the simulation results indicated that the electron localization on the dissociation process of HD + can be controlled by manipulating the laser intensity, pulse duration and the CEP of the ultrashort femtosecond pulse. Subsequently, the schemes of two femtosecond laser pulses 42–44 have been employed to explore the possibility of controlling the branching ratio to different dissociation channels of HD + by tuning the laser frequency and delay time of the two femtosecond pulses. Moreover, a multi-pulse scheme has been proposed to control the branching ratio between the different dissociation fragments of HD + .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in most of the theoretical treatments, the initial wavefunction is calculated based on the Born–Oppenheimer (B‐O) approximation (see e.g., Refs. [ ]). This approximation bases on the rationale that the nuclear kinetic energies are generally much smaller than those of electrons.…”
Section: Introductionmentioning
confidence: 99%